Introduction of a New National Currency : Policy, Institutional, and Technical Issues - Cortes Douglas, Hernan; Abrams, Richard (Washington, D.C. : International Monetary Fund, 1993)
In the last few years, a number of countries in the Former Soviet Union and Eastern Europe have become independent or regained their independence. Many have chosen to issue their own currencies and more are likely to do so. This paper draws on these and earlier experiences in order to summarize the main policy and institutional arrangements necessary for the introduction of a new currency and to discuss the key features of, and procedures for, the conversion. The paper is designed as a working document for those involved with currency reforms to help ensure that all the necessary steps are taken prior to, during, and immediately after the introduction of a new currency. The body of the paper is in four parts. First, the main macroeconomic and operational measures required to prepare for the orderly transition to the new currency are discussed, including decisions regarding the choice of exchange regime, the issuance of coupons and the costs and benefits of currency reforms. The next section covers issues relating to the production of the new currency bank notes. Next, the main features and terms of the conversion are discussed, as well as certain special issues such as speculative inflows and the treatment of banks' customers and old currency contracts. The last section covers the operation of the foreign exchange market and maintenance of exchange rate stability in the period immediately following the introduction of the new currency. The appendix covers the technical aspects of currency handling, accounting and management.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet